The Spectrum of β-thalassemia Mutations in Phitsanulok Province: Development of Multiplex ARMS for Mutation Detection - Mirasena, Saisiri; Shimbhu, Dawan; Sanguansermsri, Mondhon; Sanguansermsri, Torpong (Asian Health, Science and Technology Reports, 2007)
Because many different mutations underline the β-thalassemia, they generate a wide variety of different clinical phenotypes. An understanding of the genotype is important for medical personnel to provide proper counseling to patients and their families. Characterization of these mutations should aid the planning of prenatal diagnosis program for β-thalassemia. The heterogeneity of the mutations makes it difficult and time consuming to identify the mutation in some individuals. We developed a single-tube multiplex amplification refractory mutation system (multiplex ARMS) to identify common ethnic-specific β-thalassemia mutations. Confirmation of multiplex ARMS results was carried out using direct sequencing. Three thousand three hundred and twenty-two people from Phitsanulok province were screened for β-thalassemia trait by quantitation of HbA2 with microcolumn chromatography and characterized for the genotypes of mutations using multiplex ARMS and direct sequencing. We found that the deletion at codons 41/42 (-TCTT) was the most frequent (48%). Other mutations found in order of decreasing frequency were codon 17 (A→T) (30%), -28 (A→G) (6%) IVS-I-1(G→T) (6%), A -87 (C→A) (4%), IVS II-654 (C→T) (2%), codons 71/72 (+A) (2%) and codon 35 (C→A) (2%), respectively. These techniques were found to be a valuable tool for analysis of β-thalassemia mutations due to accurate, simple and speedy operation. An application for the diagnosis of severe thalassemia in high-risk pregnancies is promising.